Removal of cimetidine, ketoprofen and naproxen by heterogeneous catalytic ozonation over volcanic sand at low pH - Sáenz Roblero, Bryan (2020)
This work presents experimental results on the catalytic effect of volcanic sand on the simultaneous removal of naproxen, ketoprofen, and cimetidine by ozonation. Catalyst characterization included XRD, EDX, XRF, SEM and physisorption analysis. Removal assays at laboratory scale in a semi-batch reactor showed enhanced removal by the presence of the catalyst at pH 4, but no difference was found at higher pH values. Furthermore, the immobilization of different amounts of TiO2 (2.5 % and 5.0 %) on the sand surface revealed that TiO2 exerted an adverse effect on the catalytic activity at pH 4, lowering ketoprofen removal by up to 41.3 %. Likewise, the highest and fastest removal at pH 4 was obtained using a catalyst dose of 1 g/L and dosing ozone at 15 mg/L (72.5 % ketoprofen; 90.7 % total pharmaceuticals), reaching more than 80 % total elimination after only one minute of treatment. Catalyst reusability evaluated over 5 cycles demonstrated efficient elimination of the pharmaceuticals, with only slight decrease in ketoprofen elimination. Finally, heterogeneous catalytic ozonation of ketoprofen was applied in a real wastewater matrix, obtaining a removal of 75.9 % after 40 min of reaction; this represents a similar efficiency to that achieved in synthetic wastewater.